Disfunção da tuba auditiva e zumbido: um estudo da adaptação, da aplicabilidade e dos resultados de um protocolo de intervenção - Malavolta, Vitor Cantele (2023)
This research aimed to adapt a myofunctional rehabilitation protocol of the Eustachian Tube for adults, as well as to analyze it’s applicability and results, associated with the management of Allergic Rhinitis, to improve the symptoms of Eustachian Tube Dysfunction and Tinnitus. The present study was carried out at the Santa Maria Federal University and was approved by the Ethics in Research Committee under number 57700721.0.0000.5346. In the adaptation of the myofunctional protocol, the new exercises selected by the authors were sent to five expert judges in Orofacial Motricity, who needed to judge the correspondence with the exercises of the original protocol, as well as the number of executions and daily repetitions. Subjects of both genders, aged 20 to 58 years old, complaining of chronic Tinnitus and diagnosed with Eustachian Tube Dysfunction and Allergic Rhinitis participated in the study sample. In total, there were 23 subjects collected and 11 included according to the eligibility criteria. All were submitted to audiological and otorhinolaryngological evaluations to confirm the diagnosis of Eustachian Tube Dysfunction and Allergic Rhinitis as the etiological cause. To measure the effects of the intervention, the subjects were evaluated, pre and post treatment, using the Eustachian Tube Dysfunction Questionnaire, Tinnitus Matching, Tinnitus Handicap Inventory and Visual Analog Scale. The adapted protocol was performed twice a day for 30 consecutive days by the research subjects, according to the decisions of the expert judges. Allergic Rhinitis was managed with a nasal corticosteroid (Mometasone), 50 micrograms, nasal spray, two jets in each nostril, also for daily use. After 30 days, the subjects were reassessed. As results, all the expert judges agreed with the adaptation of the exercises. All subjects complied with the myofunctional protocol and the use of the medication without difficulty and without side effects. We observed a statistically significant difference in the Eustachian Tube Dysfunction Questionnaire (p=0.01), the Tinnitus Matching (p=0.02), the Tinnitus Handicap Inventory (p=0.04), and the Visual Analog Scale for loudness (p=0.02) and for annoyance (p=0.01). Finally, we can adapt the myofunctional tube rehabilitation protocol for the adult public, as well as observe it’s a good applicability and positive results associated with the etiological management of Allergic Rhinitis, in the improvement of the symptoms of Eustachian Tube Dysfunction and Tinnitus.